Experimental study of the behavioral response of fish to changes in hydrodynamic indicators in a near-natural environment - Han Liu; Junqiang Lin; Dongsheng Wang; Jin Huang; Hao Jiang; Di Zhang; Qidong Peng; Jing Yang (Ecological Indicators, 2023)
The large-scale construction of hydropower projects has significantly altered the ecohydrological conditions of fish habitats, and habitat, migration and other behavior of fish have been affected to varying degrees. Although the behavioral characteristics of fish under different hydrodynamic conditions have been investigated in a number of indoor experiments, it is still difficult to apply the results of hydrodynamic indicators directly to the practice of ecological restoration. In order to investigate the response relationship between fish behavior and hydrodynamic indicators under near-natural conditions, and to clarify the structural linkage of multiple influences between the external ecological environment, external behavior and internal changes of fish, the study relies on a large ecological test site in which the flow rate of the rivers can be changed. A low-frequency radio identification device was used in several monitoring sections in the test river to monitor the behavioral trajectories of fish in real time. The study shows that the method of fish behavior tracking based on passive integrated transponder (PIT) tags is feasible in small near-natural rivers. The test fish were more active under a low flow rate and changed their upstream trajectory in response to flow changes. When the flow velocity reached 1.6–1.8 m/s, the fish upstream gradually shifted from along the mainstream direction to along the shoreline. There was no significant difference in the activity of the test fish between day and night, with fish preferring to inhabit areas of low flow velocity and low turbulent kinetic energy. There was a range of high flow velocities (1.6–1.8 m/s) and high turbulent kinetic energy (0.1–0.15 m2/s2) that stimulated the swimming behavior of the fish. In addition, the physical indicators and physiological and biochemical indicators of fish were also included in the research scope. The test fish with high activity were slender after long-term swimming training, and their hemoglobin concentration and red blood cell number were higher than those of inactive fish and cultured fish. The research results will be used to optimize river restoration projects, promote the recovery of fish resources and population size, and reduce the negative impact of hydropower projects on the ecological environment.